Current interpretation of hormonal therapy failure in breast cancer - Szacikowska, Ewa; Kozłowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2001)
In the paper the facts and the most probable course of molecular and biological changes are presented, occurring in breast cancer cells during two successive stages of hormone treatment. The presented way of thinking is an attempt at modern interpretation of clinical facts connected with hormonal treatment, well documented since a long time. The interpretation was based on the results, of widespread basic studies conducted in recent years and available at the present level of knowledge. Particular attention was paid to deep changes in the biology of breast cancer cells, being of adaptative character and caused by estrogen ablative therapy. These processes, in view of lacking estrogens, start the potent mechanism of changes in the cell leading to switching of breast cancer cell growth regulation from endocrine and paracrine to auto/intracrine which, finally, means the progression of malignant phenotype. In the paper an attempt has been made at detailed analysis of this complicated process. It is based on several relatively recently learned facts which have rather radically changed the way of understanding breast cancer progression and well explain the failures of hormonal therapy. The constitutional transcriptional activation of estrogen receptor by peptide growth factors in the absence of estrogens is one of the most important adaptative changes being the reason of hormonal treatment failure in breast cancer, leading to intensification of cell proliferation. This is accompanied by an increase of HER2 and HER3 gene expression, caused by non-steroid antiestrogens used in antiestrogen ablation therapy, with consecutive increase in the cell of the number of receptors of growth factors encoded by these genes. The increase of the number of these receptors in the cell is highly oncogenic, since it is connected with extremely easy formation of their heterodimer complex which is one of the most aggressive oncoproteins and is responsible for an increase of intense mitogenic signalling via the ras-raf-MAPKs pathway. This intensified signalling, causing MAPKs activity increase is the direct cause of cell cycle progression and increase of cell division rate. On the other hand, the increase of HER2 and HER3 receptor expression in breast cancer cell means susceptibility increase of these cells to increased levels in the cells of autocrine produced peptide growth factors of the character of heregulins – HRGs. With progression of adaptation processes in breast cancer cells in response to their deprivation of estradiol, ever better conditions develop to more efficient action of autocrine heregulins. These processes additionally intensify the mitogenic signals going to the HER2/HER3 heterodimer by the ras-raf-MAPKs pathway, which is another cause of increasing rate of cell cycle and progression of malignant phenotype.